2020
DOI: 10.3390/ijerph17207698
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Participatory Theater Workshops to Increase Staff Awareness of and Readiness to Respond to Abuse in Health Care: A Qualitative Study of a Pilot Intervention Using Forum Play among Sri Lankan Health Care Providers

Abstract: Women globally experience mistreatment by health providers during childbirth. Researchers have identified strategies to counteract this type of abuse in health care, but few have been evaluated. We used a theater technique, Forum Play, in a brief training intervention to increase awareness of abuse in health care and promote taking action to reduce or prevent it. The intervention was implemented in four workshops with 50 participating physicians and nurses from three hospitals in Colombo, Sri Lanka. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 44 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Thirteen of the reviewed studies employed a comparative before-and-after intervention evaluation approach (19,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Eight studies used quantitative data (19,30,31,(35)(36)(37)(38)40), five studies used a mixed-methods approach (32-34, 39, 41) and three studies collected qualitative data (42)(43)(44). The 16 studies were geographically diverse, conducted in 9 countries: Tanzania (n = 2), Kenya (n = 1), Ethiopia (n = 3), Ghana (n = 3), Sri Lanka (n = 2), Brazil (n = 2), South Africa (n = 1), Sudan (n = 1), and Sweden (n = 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen of the reviewed studies employed a comparative before-and-after intervention evaluation approach (19,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Eight studies used quantitative data (19,30,31,(35)(36)(37)(38)40), five studies used a mixed-methods approach (32-34, 39, 41) and three studies collected qualitative data (42)(43)(44). The 16 studies were geographically diverse, conducted in 9 countries: Tanzania (n = 2), Kenya (n = 1), Ethiopia (n = 3), Ghana (n = 3), Sri Lanka (n = 2), Brazil (n = 2), South Africa (n = 1), Sudan (n = 1), and Sweden (n = 1).…”
Section: Methodsmentioning
confidence: 99%
“…One study selected a sample from 30 births that had been monitored using the Federal Ministry of Health of Ethiopia (FMoH) adopted Safe Childbirth Checklist (SCC) in the previous month (31). The majority of the studies focused on healthcare providers (19,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Concept (Obstetric Violence)mentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborations to other sectors, policy makers and sectors needed to address the issue of domestic violence in pregnancy. Infanti, Zbikowski et al 2020 47 Sri Lanka Urban Qualitative study Physicians and nurses from hospitals Theatre technique workshops Focus groups Content analysis Participatory theatre techniques hold potential as an intervention method for preventing and addressing abuse in health care in Sri Lanka. Various institutional barriers reported – policy and accountability system to prevent abuse in health care are not detailed, nuanced, integrated or enforced.…”
Section: Methodsmentioning
confidence: 99%
“…The participants react on the behavior of the actors, and not on the relevance of the technical gestures. Several publications in the international literature around training courses using forum theater as a tool to raise awareness of caregiver-patient and OV [12][13]15] concluded that it increased participants' ability to act on their own moral convictions and that it was an effective way to build empathy and improve team communication skills. However due to insufficient staffing levels, they did not obtain significant results in their evaluation.…”
Section: Introductionmentioning
confidence: 99%